Accessing the extent of kerogen/bitumen interactions on source rock maturation and hydrocarbon generation - Azri, Mohammad Hazwan (2013)
In order to ascertain whether kerogen and the heavy oil or bitumen generated during the initial stages of source rock maturation then go on to produce similar gas yields compared to the natural situation when they are present in source rocks, a study has been conducted on an immature type II Kimmeridge Clay Formation (KCF) source rock (Dorset, United Kingdom) with different total organic carbon contents (14, 25 and 30 % TOC), and all having an initial vitrinite reflectance (VR) of approx. 0.4 % Ro. Anhydrous and hydrous pyrolysis experiments were conducted on the whole immature source rock, the isolated partially matured bitumen-extracted source rock and the isolated bitumen (bitumen generated and extracted from the initial source rock) and mixtures of the isolated partially matured source rock and bitumen using two types of Hastalloy vessels (22 and 25 ml) at 320-420 °C for 7-48 h over a pressure range of 115-900 bar. Hydrocarbon gas yields and the increase in VR were greater from the whole rock experiments compared to the experiments on the isolated partially matured source rock and isolated bitumen (no mineral matter present), as well as the experiments on mixtures of the isolated partially matured isolated source rock and bitumen combined. The effect of particle size were also found to be of significance as higher gas yields were obtained from recombined mixture experiments using powdered samples (14 % TOC source rocks) compared to using rock chips (30 % TOC source rocks). Hydrocarbon gas yields, pyrobitumen yields, and VR values were found to decrease as pressure increases towards 500 and 900 bar compared to 180 bar at 350 °C where the effects of pressure retardation were found to be much more significant from the partially matured source rock maturation and bitumen in isolation than from the whole source rock. At 420 °C, gas generation, bitumen plus oil and coke yields were not affected by pressure, but VR decreases going from 310 bar to 500 and 900 bar. The results obtained demonstrate that the interplay of inherent mineral matter, reactant phase, source rock/kerogen, bitumen and pressure are key factors in determining the extent of hydrocarbon generation and source rock maturation in geological basins.